2010
DOI: 10.1186/1471-2458-10-111
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral treatment adherence among HIV patients in KwaZulu-Natal, South Africa

Abstract: BackgroundSuccessful antiretroviral treatment is dependent on sustaining high rates of adherence. In the southern African context, only a handful of studies (both quantitative and qualitative) have looked at the determinants including a health behaviour theory of adherence to antiretroviral therapy. The aim of this study is to assess factors including the information, motivation and behavioural skills model (IMB) contributing to antiretroviral (ARV) adherence six months after commencing ARVs at three public ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
121
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(142 citation statements)
references
References 42 publications
(53 reference statements)
14
121
1
6
Order By: Relevance
“…These adherence rates are similar to those of a study in KwaZulu-Natal using different measuring instruments. 16 Unemployment has been linked to poor adherence to ART in this study and in another South African setting. 32 These findings are not surprising as lack of finances is an enormous barrier to adherence in the African context.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These adherence rates are similar to those of a study in KwaZulu-Natal using different measuring instruments. 16 Unemployment has been linked to poor adherence to ART in this study and in another South African setting. 32 These findings are not surprising as lack of finances is an enormous barrier to adherence in the African context.…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted in KwaZulu-Natal among PLHIV attending three public hospitals showed that depression significantly increased the risk of non-adherence. 16 However, there is a lack of clinic-based data for South Africa despite the fact that the majority of people in this country access ART through clinic-based rather than hospital-based ART programmes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El nivel de adherencia adecuada encontrado en nuestro estudio es bajo (27%) y se encuentra en niveles inferiores a lo reportado por tres estudios desarrollados en Sudáfrica: 54,5%, 49,2% y 43,2% 56,57,58 . Esto podría estar relacionado al instrumento utilizado (CEAT-VIH).…”
Section: Discussionunclassified
“…Diversos estudios han mostrado la asociación entre el tiempo de infección (tiempo transcurrido desde el diagnós-tico de seropositividad al VIH) tanto con comportamientos de adhesión al tratamiento antirretroviral (Peltzer, Friend-du Prezz, Ramlagan & Anderson, 2010;Waldrop-Valverde, Jones, Jayaweera, González, Romero & Ownby, 2009) como con diversas variables biológicas y psicológicas, dentro de las que destacan el estadio clínico de infección, el afrontamiento de eventos estresantes y la percepción de apoyo social, entre otras (Gellaitry, Cooper, Davis, Fisher, Leake & Horne, 2005;Godin, Côté, Naccache, Lambert & Trottier, 2005;Heckman, Sikkema, Hansen, Kochman, Heh & Neufeld, 2010).…”
Section: Introductionunclassified